Estudo dos processos de descoloração do corante vermelho reativo 239 pelo fungo de podridão branca Trametes cingulata JUMAD075 - Cardoso, Fausto Rodrigues (2023)
The industrial textile dyeing process generates wastewater containing toxic molecules that are harmful to ecosystems. The azo dyes found in textile effluents are very dangerous for the health of human beings, as they have the azo group (N = N), reactive with nucleic acids of the DNA structure. These effluents can be treated by physical-chemical and/or biological methods. In the biological treatment of these effluents, white rot fungi can be used with a focus on two ways: the production of ligninolytic enzymes (lacase, manganese peroxidase and lignin peroxidase) for the degradation of dye molecules, and/or the adsorption of these molecules to the biomass fungal mycelium. In this sense, the aim of this research was to carry out in vivo studies for the selection of new fungi capable of performing the biodegradation of azo dyes. The fungus Trametes cingulata JUMAD075 was selected among four others, molecular characterization was carried out and led to further studies and optimization of cultivation conditions for biodegradation. The fungus showed laccase activity of 10.69 U/mL and 40% decolorization of the azo dye Reactive Red 239 (0.2 g/L) in 12 days. Optimization of fungus cultivation conditions was carried out through a multifactorial experimental design, for greater responses of enzymatic activity and azo dye decolorization. The ideal supplementation of copper sulfate (2.5 g/L), yeast extract (8.5 g/L) and cultivation time (12 days) was identified, with a production of 10.290 U/mL of laccase, of 0.016 U/mL of lignin peroxidase, 0.003 U/mL of manganese peroxidase and 64% decolorization (w/v) under optimized conditions. An experiment was carried out to analyze the efficiency in discoloration with a pool of 1% (w/v) enzymes (lacase activity of 7.332 U/mL) extracted from optimized cultivation, with a decrease of an average of 34% in the color of the dye. The fungal biomass was analyzed by Fourier transform infrared spectroscopy, identifying a possible adsorption of functional groups of the dye to the fungal mycelium. In scanning electron microscopy analyses, images were obtained that allow differentiating aspects that suggest the adsorption pathway. It was possible to conclude that the microorganism T. cingulata JUMAD075 has the capacity to perform the treatment of effluents containing azo dyes, being able to act, by two ways, the biosorption to the fungal mycelium and the enzymatic biodegradation.